Power to the People : Evidence from a Randomized Field Experiment of a Community-Based Monitoring Project in Uganda - Björkman, Martina; Svensson, Jakob (World Bank, Washington, DC, 2012)
This paper analyzes the importance of strengthening the relationship of accountability between health service providers and citizens for improving access to and quality of health care. How this is to be achieved, and whether it works, however, remain open questions. The paper presents a randomized field experiment on increasing community-based monitoring. As communities began to more extensively monitor the provider, both the quality and quantity of health service provision improved. One year into the program, there are large increases in utilization, significant weight-for-age z-score gains of infants, and markedly lower deaths among children. The findings on staff behavior suggest that the improvements in quality and quantity of health service delivery resulted from an increased effort by the staff to serve the community. Overall, the results suggest that community monitoring can play an important role in improving service delivery when traditional top-down supervision is ineffective.